Pewarisan Budaya dalam Pengembangan Ekonomi Masyarakat - Ruslan Sudrajat (TEMALI : Jurnal Pembangunan Sosial, 2020)
This study aims to determine the process of cultural inheritance in society. This study also aims to determine the community's response to cultural phenomena and economic developments that are currently happening. The theory used to analyze this research is the theory of cultural inheritance from Hari Poerwanto about the processes and forms of inheritance and the theory from Pierre Bourdieu about habitus, capital, and arenas, which are related to the survival of a community group. This study uses a qualitative method with a descriptive approach in which data is obtained directly from the object of research. This data was collected using techniques: observation, interviews, and literature study. The research results found in Kelurahan Regol, Garut, West Java show that the process of cultural inheritance occurs where the environment in which there is a community group tends to dominate. Culture as the habitus of society has not yet supported the progress of the community's economy because the social capital they have is less able to bet on an increasingly competitive arena. Thus, it causes a weak economic culture related to society's passive response when it collides with cultural phenomena and economic development that is not progressing.